Environmental fate and transport analysis with compartment modeling - Little, Keith W. (Boca Raton, FL. : CRC Press, 2012)
'This book examines mathematical modeling and computer simulations that estimate the distribution of chemical contaminants in environmental media in time and space. Discussing various modeling issues in a single volume, this text provides an introduction to a specific numerical modeling technique called the compartment approach and offers a practical user's guide to the GEM. It includes the Generic Environmental Model (GEM) software package, which implements the techniques described. The author presents algorithms for solving linear and nonlinear systems of algebraic equations as well as systems of linear and nonlinear partial differential equations'--
Includes bibliographical references and index.
Keywords: Pollution -- Mathematical models; Transport theory -- Mathematical models; Diffusion -- Mathematical models; Cross-media pollution; Compartmental analysis (Biology); Pollutants; Differential equations